Efektivitas Konseling Kelompok dengan Terknik Cognitive Restructuring untuk Mengurangi Academic Burnout pada Mahasiswa: Penelitian - Meutia Nathonia Sufairok; Abdur Razzaq; Bela Janare Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The accounting period postulate is a foundational principle that divides an This article discusses a literature review: regarding the effectiveness of group counseling with cognitive restructuring techniques to reduce academic burnout in Islamic Guidance Counseling students which aims to determine the effectiveness of group counseling with cognitive restructuring techniques to reduce academic burnout in Islamic Guidance Counseling students at Raden Fatah State Islamic University, Palembang. The method used in this study uses a quantitative pre-experimental method with one group pretest-posttest design. The research sample is 10 students. Data collection techniques are observation, questionnaires, documentation. Data analysis techniques used are validity test, reliability test, normality test, Wilcoxon test. The results of this study indicate that the test results using IBM Statistics SPSS 26 have an Asymp.Sig. (2-tailed) value of 0.005. Because the Asymp.Sig. (2-tailed) value is smaller <0.05, then Ha is accepted and Ho is rejected, so group counseling with cognitive restructuring techniques is effective in reducing academic burnout in Islamic guidance counseling students at Raden Fatah State Islamic University, Palembang.